Light‐Mediated Seleno‐Functionalization of Organic Molecules: Recent Advances. Issue 10 (3rd March 2021) - Rafique, Jamal; Rampon, Daniel S.; Azeredo, Juliano B.; Coelho, Felipe L.; Schneider, Paulo H.; Braga, Antonio L.
Abstract: Organoselenium compounds constitute an important class of substances with applications in the biological, medicinal and material sciences as well as in modern organic synthesis, attracting considerable attention from the scientific community. Therefore, the construction of the C−Se bond via facile, efficient and sustainable strategies to access complex scaffolds from simple substrates are an appealing and hot topic. Visible light can be regarded as an alternative source of energy and is associated with environmentally‐friendly processes. Recently, the use of visible‐light mediated seleno‐functionalization has emerged as an ideal and powerful route to obtain high‐value selenylated products, with diminished cost and waste. This approach, involving photo‐excited substrates/catalyst and single‐electron transfer (SET) between substrates in the presence of visible light has been successfully used in the versatile and direct insertion of organoselenium moieties in activated and unactivated C(sp 3 )−H, C(sp 2 )−H, C(sp)−H bonds as well as C−heteroatom bonds. In most cases, ease of operation and accessibility of the light source (LEDs or commercial CFL bulbs) makes this approach more attractive and sustainable than the traditional strategies. Abstract : This account highlights recent progress in the photoinduced seleno‐functionalization of various biologically‐relevant organic molecules for the synthesis of a diverse range of useful selenylated products. Visible light‐mediated organic‐transformations has emerged as an efficient and environmentally compatible synthetic strategy in modern organic synthesis. Due to its simplicity and mildness, in recent years, there is an increase of interest in the photoinduced C−Se bond functionalization.